Experimental study of slow-released Angiogenin by silicon micro-needle in improving blood support to multiple-territory perforator flaps in rats: Silicon micro-needle in slow-released Angiogenin - Liu, Xiaojun; Wang, Xue; Zhao, Rui; Liu, Yunfeng; Chen, Wei; Su, Jiandong; Shen, Guoliang (Cellular and Molecular Biology, 2024)
This research aimed to investigate the effect of slow-released angiogenin by silicon micro-needle on angiogenesis in the Choke zone of dorsal multiple-territory perforator flap in rats, as well as its mechanism. Thirty-six adult Sprague-Dawley (SD) rats were randomly divided into control group, model group, and four experimental groups. In model group, slow-release saline through a silicon micro-needle was placed in choke II zone of the flap 7 days before the operation. For rats in four experimental groups, angiogenin was released via micro-needle in the choke I and choke II zones of the cross-zone flap 7 days before and 3 days before flap surgery, respectively. A 12 cm × 3 cm cross-zone perforator flap model was made on the back of all five groups. The flap survival rate in slow-release angiopoietin group was statistically higher than that in model group (P<0.05). Angiogenin in choke zone of the flap was increased in slow-release angiogenin group (P<0.05). In slow-release angiogenin group, the micro-vessel density was increased and the arteriovenous diameter was decreased, while the arteriovenous diameter was increased in model group (P<0.05). The levels of vascular endothelial growth factor A (VEGF-A) and angiotensin 1 (ANG-1) in choke zone were both elevated in slow-release angiogenin group (P<0.05). The expression of CD31 was significantly elevated in flaps of experimental groups (P<0.05). Micro-needle to slow release Angiogenin can increase the drug concentration in the tissues of the choke zone, promote the vascularization of rat dorsal crossover area perforator flap, reduce the possibility of flap ischemic necrosis, and improve the flap survival rate.